2007
DOI: 10.1016/j.neuron.2007.06.019
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Switch in Subunit Composition of a Chromatin Remodeling Complex during Neural Development

Abstract: Mammalian neural stem cells (NSCs) have the capacity to both self-renew and to generate all the neuronal and glial cell-types of the adult nervous system. Global chromatin changes accompany the transition from proliferating NSCs to committed neuronal lineages, but the mechanisms involved have been unclear. Using a proteomics approach, we show that a switch in subunit composition of neural, ATP-dependent SWI/SNF-like chromatin remodeling complexes accompanies this developmental transition. Proliferating neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
806
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 679 publications
(841 citation statements)
references
References 54 publications
28
806
1
6
Order By: Relevance
“…However, we also note that regulators of DNA methylation are required for the function of a variety of adult stem cells (Zhao et al, 2003;Ma et al, 2009;Trowbridge et al, 2009;Sen et al, 2010;Trowbridge and Orkin, 2010;Wu et al, 2010), and that they complex with chromatin modifiers to elicit changes in chromatin state (Jones et al, 1998;Nan et al, 1998;Fuks et al, 2003). In addition, chromatin remodeling factors are also important for stem and progenitor cell function (Lessard et al, 2007;Ho et al, 2009;Ho and Crabtree, 2010), suggesting that several epigenetic mechanisms could coordinately control adult stem cell gene expression programs during organismal aging.…”
Section: Epigenetic Regulation Of Aging Stem Cellsmentioning
confidence: 71%
“…However, we also note that regulators of DNA methylation are required for the function of a variety of adult stem cells (Zhao et al, 2003;Ma et al, 2009;Trowbridge et al, 2009;Sen et al, 2010;Trowbridge and Orkin, 2010;Wu et al, 2010), and that they complex with chromatin modifiers to elicit changes in chromatin state (Jones et al, 1998;Nan et al, 1998;Fuks et al, 2003). In addition, chromatin remodeling factors are also important for stem and progenitor cell function (Lessard et al, 2007;Ho et al, 2009;Ho and Crabtree, 2010), suggesting that several epigenetic mechanisms could coordinately control adult stem cell gene expression programs during organismal aging.…”
Section: Epigenetic Regulation Of Aging Stem Cellsmentioning
confidence: 71%
“…Combinatorial assembly of SWI/SNF subunits into structurally and functionally diverse CRCs is connected to the control of key pathways in mammalian development (Lessard et al 2007). Analogously, CRCs carrying diVerent combinations of Snf2-type ATPases with SNF5/BSH and homo-or heterodimeric forms of diVerent ATSWI3 subunits have been implicated in various developmental processes in Arabidopsis (Jerzmanowski 2007;Kwon and Wagner 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This last result implicated the Swi/Snf complex in neuronal differentiation, and it has recently been demonstrated that a switch of the components from this complex is related to the transition of NSC to neurons (Lessard et al, 2007). In this context, it is possible that ICD participates in such a switch.…”
Section: Discussionmentioning
confidence: 83%